2023
DOI: 10.1038/s41598-023-49492-5
|View full text |Cite
|
Sign up to set email alerts
|

Mild internet use is associated with epigenetic alterations of key neurotransmission genes in salivary DNA of young university students

Eugenia Annunzi,
Loreta Cannito,
Fabio Bellia
et al.

Abstract: The potentially problematic use of the Internet is a growing concern worldwide, which causes and consequences are not completely understood yet. The neurobiology of Internet addiction (IA) has attracted much attention in scientific research, which is now focusing on identifying measurable biological markers. Aim of this study was to investigate epigenetic and genetic regulation of oxytocin receptor (OXTR), dopamine transporter (DAT1) and serotonin transporter (SERT) genes using DNA obtained from saliva samples… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…Therefore, adolescents with co-morbid Internet addiction and depressive symptoms appear to be at a vulnerable stage and are experiencing a deterioration in development due to the mutually malignant effects of Internet addiction and depressive symptoms. This, to some extent, supports both the compensatory Internet use theory (15) and the social displacement hypothesis (16), which is also consistent with recent research implying the existence of shared neurobiological mechanisms, such as oxytocinergic and dopaminergic expression, between Internet addiction and depressive symptoms (82,83). Notably, this finding emphasizes that the initial year of junior high school is a particularly critical period for detecting Internet addiction and depressive symptoms, as well as a pivotal opportunity for preventing the deterioration of Internet addiction and depressive symptoms.…”
Section: Joint Developmental Trajectories Of Internet Addiction and D...supporting
confidence: 90%
“…Therefore, adolescents with co-morbid Internet addiction and depressive symptoms appear to be at a vulnerable stage and are experiencing a deterioration in development due to the mutually malignant effects of Internet addiction and depressive symptoms. This, to some extent, supports both the compensatory Internet use theory (15) and the social displacement hypothesis (16), which is also consistent with recent research implying the existence of shared neurobiological mechanisms, such as oxytocinergic and dopaminergic expression, between Internet addiction and depressive symptoms (82,83). Notably, this finding emphasizes that the initial year of junior high school is a particularly critical period for detecting Internet addiction and depressive symptoms, as well as a pivotal opportunity for preventing the deterioration of Internet addiction and depressive symptoms.…”
Section: Joint Developmental Trajectories Of Internet Addiction and D...supporting
confidence: 90%
“…Notably, within the low-risk groups (Figure 5A), the CpG 6 (correla�ng with CpGs 2 and 3) was nega�vely correlated to CpG 5; although this effect was not significant, this may be due to the lower numerosity of this low-risk group. S�ll, we repeatedly found an�-correla�on of CpG 5 on one side with CpGs 3 and 6 on the other hand, in control or low-risk groups in other studies (see (Annunzi et al, 2023;Nardi et al, 2020).…”
Section: Dna Methyla�on Studiessupporting
confidence: 52%
“…In par�cular, we report in highly sensi�ve subjects with higher PSS scores when compared to those less stressed, an increase in DNA methyla�on at one specific CpG site (number 5) at gene 5'UTR, and it is known that this epigene�c mechanism is associated with a reduc�on in gene expression since prevents the binding of transcrip�on factors to DNA (Robertson, 2005). DNA methyla�on of the human DAT1 gene has been extensively inves�gated since 80% of its promoter is formed by GCs sequences and it has mul�ple CpG islands (Bannon et al, 2001;Shumay et al, 2010), and altera�ons in gene epigene�c mark have been reported in different phenotypes pathological and not (Adriani et al, 2018;Annunzi et al, 2023;Chmielowiec et al, 2023;Song et al, 2014), showing at specific CpG sites both reduc�ons, as well as increases, as we here report (Chmielowiec et al, 2023;Hillemacher et al, 2009;Rubino et al, 2020). In par�cular, the transi�on from an�-correla�on in low-risk towards direct correla�on in high-risk subjects, as far as CpGs 3 (or 6) and 5 are concerned, was similarly found in our previous studies on internet addic�on (Annunzi et al, 2023;Nardi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation